2018
DOI: 10.1016/j.freeradbiomed.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Selenite and methylseleninic acid epigenetically affects distinct gene sets in myeloid leukemia: A genome wide epigenetic analysis

Abstract: Selenium compounds have emerged as promising chemotherapeutic agents with proposed epigenetic effects, however the mechanisms and downstream effects are yet to be studied. Here we assessed the effects of the inorganic selenium compound selenite and the organic form methylseleninic acid (MSA) in a leukemic cell line K562, on active (histone H3 lysine 9 acetylation, H3K9ac and histone H3 lysine 4 tri-methylation, H3K4me3) and repressive (histone H3 lysine 9 tri-methylation, H3K9me3) histone marks by Chromatin im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Cell adhesion is gaining more attention due to its implication in cancer metastasis and progression, in addition to drug resistance. Importantly, these results are in accordance with recent investigations revealing that MSA targeted adhesion molecules in a leukemic cancer cell line, whereas inorganic selenite affected other gene sets, indicating an interesting type-dependent effect of Se compounds [ 34 ]. To further confirm the compound-induced adhesion disturbance, levels of different adhesion molecules were screened 24 h after treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Cell adhesion is gaining more attention due to its implication in cancer metastasis and progression, in addition to drug resistance. Importantly, these results are in accordance with recent investigations revealing that MSA targeted adhesion molecules in a leukemic cancer cell line, whereas inorganic selenite affected other gene sets, indicating an interesting type-dependent effect of Se compounds [ 34 ]. To further confirm the compound-induced adhesion disturbance, levels of different adhesion molecules were screened 24 h after treatment.…”
Section: Discussionsupporting
confidence: 91%
“…This might partly explain the survival of immune cells upon treatment with selenite. MSA has however been reported in several studies to act via redox modulatory effects that do not mainly cause oxidative stress to the cells ( 28 ). In line with these previous studies, MSA did not trigger any Nrf2 response, indicating that immune cell resistance to MSA is achieved by a different molecular mechanism, again illustrating the distinct effect encompassed by each separate selenium metabolite ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that MSA affect a large set of genes involved in the loss of attachment of cells to the extracellular matrix. Among the many genes identified, several of the matrix metalloproteineases (MMPs) were found to be significantly upregulated in response to MSA ( 28 ). Methylselenol, the active metabolite of MSA, was also identified by Zeng and co-workers to activate MMP-2 and MMP-9 ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an organic Se, MSA has few side effects, has excellent anticancer effects, and is easily absorbed compared to inorganic Se. 17,32 For example, MSA can reduce cell number in a dose-dependent manner. The inhibitory effect was equivalent to a 10-fold greater concentration of methyl selenocysteine acid, and the reaction was more pronounced and faster.…”
Section: Discussionmentioning
confidence: 99%